1995
DOI: 10.1246/cl.1995.641
|View full text |Cite
|
Sign up to set email alerts
|

Novel Ferroelectric Liquid Crystals Derived from Trifluoromethylated Pyranoses Showing Very Large Spontaneous Polarization

Abstract: Novel ferroelectric liquid crystals with a trifluoromethylated pyranose were synthesized and their mesomorphic properties were investigated. These compounds exhibited a chiral smectic C phase and showed very large spontaneous polarization over 700 nC·cm−2. Relationships between molecular structures and physical properties were discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1998
1998
2007
2007

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Although the SmCi phase is not exhibited by the guest compounds themselves, Itoh et al [60,61]* have clearly confirmed the appearance of the SmCi in the mixture, the composition of which is specified in Figure 33, by observing the typical tristable switching. This finding is very important, suggesting as it does the possibility of developing practical guest-host type mixtures of AFLC materials.…”
Section: Antiferroelectric Liquid Crystal Compounds With Unusual Chemmentioning
confidence: 92%
“…Although the SmCi phase is not exhibited by the guest compounds themselves, Itoh et al [60,61]* have clearly confirmed the appearance of the SmCi in the mixture, the composition of which is specified in Figure 33, by observing the typical tristable switching. This finding is very important, suggesting as it does the possibility of developing practical guest-host type mixtures of AFLC materials.…”
Section: Antiferroelectric Liquid Crystal Compounds With Unusual Chemmentioning
confidence: 92%
“…Since the discovery of the antitumor activity of uracil with a fluorine, research for the modification of molecules with fluorine(s), which played a significant role on their biological activities or stabilities, has been extensive. In particular, optically active fluorine-containing molecules have been recognized as quite an important class of materials because of their interesting characteristics and potential applicability to optical devices . We have devoted our attention to the synthesis of functionalized chiral building blocks with a fluoroalkyl moiety for attaining ready access to these types of molecules in a highly efficient manner.…”
mentioning
confidence: 99%